Pengaruh Daya Tarik Objek Wisata, Akomodasi, dan Motif Wisata Terhadap Kepuasan Wisatawan di Pulau Tidung Kepulauan Seribu Jakarta - Ruhil Easoci; Parlagutan Silitonga; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2017)
The purpose of this research is to analyze the influences of tourist attraction, accommodation and tourist motive toward tourists satisfaction in Tidung of Thousand Islands Jakarta. It also aims to determine the most dominant variabel contribute to tourist satisfaction. The data were collected by distributing questionnaires to 100 respondents in Tidung Island, using accidental sampling technique. The analysis used for this research is multiple linear regression. The result of the research shows that those variabels partially and simultaneously affect toward tourists satisfaction and also contribute 37.45% for it. Among variabels, tourist attraction also becomes the most dominant variabel to affect tourists satisfaction.